Elaboración de un material compuesto por una matriz de resina poliéster y fibra natural de coco para su caracterización mecánica a tensión y flexión. (2022)
This work is based on the development of a material composed of a matrix of polyester resin and natural coconut fiber, for its mechanical characterization in tensile and flexural. Taking into account the orientation of the reinforcement; in three directions at 0°, 45° and 90° (vertical, diagonal and horizontal) respectively. It was investigated based on different bibliographic sources. Therefore, in the first stage of the project, the theoretical bases are found where the classification of composite materials and natural fibers is explained, as well as the physical-mechanical properties of polyester resin and coconut fiber.